Sulfur Removal in Bio-Briquette Combustion Using Seashell Waste Adsorbent at Low Temperature - Mahidin, Mahidin; Gani, Asri; Muslim, Abrar; Husin, Husni; Hani, M. Reza; Syukur, Muhammad; Hamdani, Hamdani; Khairil, Khairil; Rizal, Samsul (ITB Journal Publisher, LPPM ITB, 2016)
Presently, biomass is mostly utilized as co-fuel in coal combustion in view of energy diversification and emission reduction. However, since the coal content of bio-briquettes is high (up to 80% in this study), gas emissions such as those of SOx still occur. Therefore, the introduction of SO2adsorbent is common in coal briquette or bio-briquette combustion. A calcium-based material is usually used for this goal. The aim of this study was to observe the effects of desulfurization temperature and Ca/S ratio (Ca = calcium content in adsorbent; S = sulfur content in coal and biomass) on desulfurization efficiency and kinetics. The ratio of coal to biomass (palm kernel shell/PKS) was fixed at 90:10 (wt/wt) and the ratios of Ca to S were varied at 1:1, 1.25:1, 1.5:1, 1.75:1 and 2:1. The mixtures of coal, PKS and adsorbent were briquetted at a molding pressure of 6 ton/cm2 with Jatropha curcas seeds and starch mixture as binding agents. Desulfurization was performed within a temperature range of 300 to 500Â°C for 720 seconds at an airflow rate of 1.2 L/min. The results showed that the highest desulfurization efficiency (90.6%) was associated with the Ca/S ratio of 2:1 and temperature of 400Â°C. Moreover, the highest reaction rate constant of desulfurization was 0.280 min-1.